PENAKSIR RASIO DAN PENAKSIR REGRESI YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN DEVIASI KUARTIL DAN KOEFISIEN SKEWNESS - Linda Veronika; Sigit Sugiarto; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article the combination of ratio estimators and ratio-regression in simple random sampling using quartile deviation and coefficient of skewness are discussed, which is a review from the article Jeelani et.al. [International Journal of Modern Mathematical Sciences, 6(3): 174-183]. These estimators are biased estimators and their mean square errors are determined. Estimator with the smallest mean square error is the most efficient estimator. A numerical example is given at the end of discussion.